Characteristics of Effective Intercultural Multimedia Material in the English Language Class - Diana Jánica; Lourdes Rey; Nayibe Rosado (Asociación Colombiana de Profesores de Ingles, 2006)
This paper describes a research study aimed at identifying the characteristics that multimedia material should have in order to promote the development of intercultural competence in undergraduate students at the Universidad del Norte in Barranquilla, Colombia (Uninorte). Specific pedagogical and technological features were explored in this research. Results showed that the use of the ICT (Information Communication Technologies) promotes the development of intercultural competence; facilitates self-directed learning processes and increases motivation. Findings also led to the definition of very specific features for this type of material.